A new species of Drymaeus endemic from Currais Archipelago, Paraná, Brazil (Pulmonata, Bulimulidae) - Simone, Luiz Ricardo Lopes de; Belz, Carlos Eduardo; Gernet, Marcos de Vasconcellos (Papéis Avulsos de Zoologia, 2020)
The new bulimulid species, Drymaeus currais sp. nov., is described based on shell and anatomical features. It is endemic of Guapirá Island, belonging to the Currais Archipelago, a small protected area off Paraná coast. The species is thus, based at least on endemicity, endangered. It has as closest species D. castilhensis, another endemic species of Castilho Island, ~70 km northwards. Its main exclusivities are a banded shell (except for periumbilical area); a ureter ~1/3 opened (furrow); an external anus; a slightly different buccal and intestinal arrangement; a penis lacking internal chambers; a small receptacle with a genital appendix. Zoobank Register: urn:lsid:zoobank.org:pub:25B25A8B-CED0-4284-A799-5383998BE481.